Odpowiedź :
Oblicz wartości liczbowe wyrażeń.
a) 3(x²− 3x + 5) − 14(12x² + 4x − 20) dla x = −1,6
3[(-1,6)² - 3*(-1,6) + 5] - 14[12(-1,6)² + 4*(-1,6) - 20] = 3(2,56 + 4,8 + 5) - 14(12*2,56 - 6,4 - 20) = 3(12,36) - 14(30,72 - 6,4 - 20) = 3(12,36) - 14(4,32) = 37,08 - 60,48 = -23,4
b) y(3xy + 4x) − x(4y² + 4y − 2x) dla x = 10, y = −0,6
-0,6[3*10*(-0,6) + 4*10] - 10[4*(-0,6)² + 4*(-0,6) - 2*10] = -0,6(-18 + 40) - 10(4*0,36 - 2,4 - 20) = -0,6(22) - 10(1,44 - 2,4 - 20) = -0,6(22) - 10(-20,96) = -13,2 + 209,6 = 196,4